Hubungan Antara Gaya Kepemimpinan Kepala Sekolah Terhadap Efektivitas Supervisi di Sekolah Menengah Kejuruan (SMK) - Marfuah, Marfuah; Sururi, Sururi (Universitas Negeri Malang, 2024)
Abstract: This study aims to analyze the relationship between the principal's leadership style and the effectiveness of supervision in Vocational High Schools (SMK). The research method used is a quantitative approach with a correlational design. The research sample consisted of 100 vocational school teachers who were randomly selected from five vocational schools in City Bandung Barat. Data were collected using questionnaires on the principal's leadership style and the effectiveness of supervision that had been tested for validity and reliability. Data analysis used Pearson correlation techniques and simple linear regression. The results showed that there was a significant positive relationship between the principal's leadership style and the effectiveness of supervision (r = 0.78; p < 0.05). The transformational leadership style had the strongest correlation with the effectiveness of supervision (r = 0.82; p < 0.05), followed by the democratic leadership style (r = 0.75; p < 0.05), and the autocratic leadership style (r = 0.68; p < 0.05). The results of the regression analysis showed that the principal's leadership style contributed 60.8% to the effectiveness of supervision. These findings emphasize the importance of the principal's leadership style in improving the effectiveness of supervision in vocational schools. Keywords: leadership style, principal, effectiveness of supervision, vocational school Abstrak: Penelitian ini bertujuan untuk menganalisis hubungan antara gaya kepemimpinan kepala sekolah dengan efektivitas supervisi di Sekolah Menengah Kejuruan (SMK). Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan desain korelasional. Sampel penelitian terdiri dari 100 guru SMK yang dipilih secara acak dari lima SMK di Kabupaten Bandung Barat. Data dikumpulkan menggunakan kuesioner gaya kepemimpinan kepala sekolah dan efektivitas supervisi yang telah diuji validitas dan reliabilitasnya. Analisis data menggunakan teknik korelasi Pearson dan regresi linier sederhana. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara gaya kepemimpinan kepala sekolah dengan efektivitas supervisi (r = 0,78; p < 0,05). Gaya kepemimpinan transformasional memiliki korelasi paling kuat dengan efektivitas supervisi (r = 0,82; p < 0,05), diikuti oleh gaya kepemimpinan demokratis (r = 0,75; p < 0,05), dan gaya kepemimpinan otokratis (r = 0,68; p < 0,05). Hasil analisis regresi menunjukkan bahwa gaya kepemimpinan kepala sekolah berkontribusi sebesar 60,8% terhadap efektivitas supervisi. Temuan ini menekankan pentingnya gaya kepemimpinan kepala sekolah dalam meningkatkan efektivitas supervisi di SMK Bandung Barat. Kata kunci: gaya kepemimpinan, kepala sekolah, efektivitas supervisi, SMK